Ujaran kebencian netizen Indonesia dalam kolom komentar Instagram selebgram Indonesia: Sebuah kajian linguistik forensik - Febry Ramadani S (Aksara: Jurnal Bahasa dan Sastra, 2021)
AbstractThis study aims to discuss in more depth the utterances of hate Indonesian netizens in the Rahmawati Kekeyi Putri Cantikka Instagram comment column which were examined using forensic linguistic analysis. This research is a qualitative study using a forensic linguistic approach. Where data collection is obtained by observing and analyzing the evidence of language crimes in the form of hate speech of Indonesian netizens in the Rahmawati Kekeyi Putri Cantikka Instagram comment column. The results revealed that there were 15 netizens' utterances from 22 analyzed data that could be said to be valid and then said to be utterances of hatred, as stated in article 27 paragraph (3) juncto Article 45 paragraph (1) of RI Law No. 9/2016 concerning Limitation of Law Number 11 Year 2008 concerning Information and Electronic Transactions (ITE).Keywords: hate speech, Instagram social media, forensic linguistics.